2005
DOI: 10.1029/2005eo500002
|View full text |Cite
|
Sign up to set email alerts
|

Crater glaciers on active volcanoes: Hydrological anomalies

Abstract: Mount St. Helens is an active volcano that hosts glacier ice within its crater. Although the common picture of volcano/glacier interactions is one of rapid meltwater generation when hot material is brought into contact with snow and ice [e.g.,Major and Newhall, 1989], there have been practically no observable hydrological consequences of the ongoing episode of silicic lava dome emplacement at Mount St. Helens. The glaciological consequences have nonetheless been dramatic: The crater glacier has been cut in hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This atypical location for crevasse development suggests that the form could be related to a locally confined heat source, e.g. a fumarole beneath the glacier, where geothermal heat flux is considerably higher (Welch et al, 2007). No vapour or sulfur smell was observed at this location but the influence of volcanic heat flow on glacier retreat at El Pecho is supposed to contribute to the ablation.…”
Section: Volcanic Influencementioning
confidence: 92%
See 1 more Smart Citation
“…This atypical location for crevasse development suggests that the form could be related to a locally confined heat source, e.g. a fumarole beneath the glacier, where geothermal heat flux is considerably higher (Welch et al, 2007). No vapour or sulfur smell was observed at this location but the influence of volcanic heat flow on glacier retreat at El Pecho is supposed to contribute to the ablation.…”
Section: Volcanic Influencementioning
confidence: 92%
“…The lahars simulated in this study represent debris flow types with sediment concentrations similar to the observed ice-melt-triggered lahars on Popocatépetl in City, the study area and Puebla is derived from SRTM3 elevation model. The dotted area shown as 'prehispanic lahars' represent the approximate extent of areas flooded by repeated lahar events from Popocatépetl, Iztaccíhuatl and La Malinche after Siebe et al (1996). al., 1998; Julio Miranda and Delgado Granados, 2003;Sheridan et al, 2005;Walder et al, 2005;Hubbard et al, 2006;Davila et al, 2007;Huggel et al, 2008). By applying such tools to Iztaccíhuatl volcano in Mexico, we show how an initial hazard evaluation can be carried out relatively fast and at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Regional climate models for the state of Washington, for example, suggest significant warming with up to 71% loss of snowpack by 2060 (Salathé et al, 2010). Over the coming decades, glacial meltwater captured by permeable surface deposits could possibly increase liquid saturation and elevate pore pressures within an edifice (Carrasco-Núñez et al, 1993;Walder et al, 2005). Acid sulfate alteration of edifice rocks could be enhanced by a slow steady supply of glacier melt water combining with ascending acidic gases from depth (Carrasco-Núñez et al, 1993).…”
Section: Future Modeling Directionsmentioning
confidence: 99%
“…To explain why the downstream portion of East Crater Glacier remains largely stagnant during the squeezing event while the upstream portion undergoes dramatic changes, Walder and others (2005) suggested that ice in the downstream portion of the glacier, which was not squeezed, acted as a dam against the ice upstream. We augment their qualitative discussion by using the model to understand quantitatively why a dam would form.…”
Section: Resultsmentioning
confidence: 99%
“…3), however, was only a factor of 3–4. Walder and others (2005) suggested an explanation: the lower third of the glacier, which was not squeezed, acted as a dam that pushed back against the ice upstream. This would lead to a large, longitudinal stress gradient.…”
Section: Introductionmentioning
confidence: 99%